2009
DOI: 10.1002/mar.20289
|View full text |Cite
|
Sign up to set email alerts
|

How to repair customer trust after negative publicity: The roles of competence, integrity, benevolence, and forgiveness

Abstract: The purpose of the comprehensive model presented here is to explain the underlying mechanism by which corporations can repair customer trust after negative publicity. The study sets out to examine corporate informational, affective, and functional initiatives managers take to influence three trustworthiness factorscompetence, benevolence, and integrity-and to elicit forgiveness. A scenario-based experiment conducted to test the conceptual model found support for most hypotheses. According to the results, rebui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
325
0
15

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(352 citation statements)
references
References 48 publications
12
325
0
15
Order By: Relevance
“…The participants outlined that, as in their private life, they were more likely to forgive one celebrity over another due to the level of their emotional connection and affinity with them (Escalas & Bettman, 2009b;Houran, Navik, & Zerrusen, 2005 This indicates that, contrary to a reciprocal relationship, the celebrity does not have to 'like back' for forgiveness to happen. This even goes further, as the celebrity-consumer dynamic shows tendencies that highlight an interdependence between forgiveness and commitment due to a consumer's reliance on the para-social relationship (Chung & Beverland, 2006;Xie & Peng, 2009). This is interesting insofar as, when forgiveness is provided, a relationship that is de facto inexistent or only 'alive' as an imagined one, is 're-established' or 'maintained'.…”
Section: Consumer-related Driversmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants outlined that, as in their private life, they were more likely to forgive one celebrity over another due to the level of their emotional connection and affinity with them (Escalas & Bettman, 2009b;Houran, Navik, & Zerrusen, 2005 This indicates that, contrary to a reciprocal relationship, the celebrity does not have to 'like back' for forgiveness to happen. This even goes further, as the celebrity-consumer dynamic shows tendencies that highlight an interdependence between forgiveness and commitment due to a consumer's reliance on the para-social relationship (Chung & Beverland, 2006;Xie & Peng, 2009). This is interesting insofar as, when forgiveness is provided, a relationship that is de facto inexistent or only 'alive' as an imagined one, is 're-established' or 'maintained'.…”
Section: Consumer-related Driversmentioning
confidence: 99%
“…Driessens, 2012;Turner, 2014). Issues arise when mismatches occur between the luminary's portrayed public image and their 'true colours' as it decreased participants' willingness to forgive and influenced perceived connections to the celebrity, with regards to trustworthiness and commitment (Pornpitakpan, 2003(Pornpitakpan, , 2004Xie & Peng, 2009 Other participants like Sandy indicated that the bigger the perceived mismatch the bigger the perceived betrayal. Yet, if the transgression 'matched' the celebrity's perceived image, participants tended to overlook the misdemeanour and were more lenient due to the congruency between person and behaviour as the celebrity was 'still in character': Ability to disentangle the private and professional persona of the celebrity In contrast to private relationships, where private and professional persona can be more closely intertwined and both be experienced in person, this differs for celebrities.…”
Section: Celebrity-related Driversmentioning
confidence: 99%
“…between two individuals who know each other personally, it can easily be generalized to account for the relationship between a company and its stakeholders (e.g. Caldwell and Clapham, 2003;Greenwood and Van Buren III, 2010;Ingenho↵ and Sommer, 2010;Schoorman et al, 2007;Xie and Peng, 2009). As Ingenho↵ and Sommer (2010: 342) note, "[t]he origin of trust lies in the individual, whereas the referent, the trusted party, can be both individual and collective".…”
Section: Mayer Davis and Shoorman's Model Of Trustmentioning
confidence: 99%
“…XIE;PENG, 2009;LAER;RUYTER, 2010). Ademais, poucos foram os trabalhos que avaliaram a recuperação da confiança após múltiplas falhas ou múltiplas violações (p. ex.…”
Section: Delimitação Do Tema E Definição Do Problemaunclassified
“…Ressalta-se que alguns estudos apresentam um esforço neste sentido (p. ex. XIE;PENG, 2009;LAER;RUYTER, 2010), porém com enfoque em violações únicas, ou seja, na recuperação da confiança após uma única falha, e no contexto de publicidade negativa (XIE; PENG, 2009) e comunicações em blogs de referências (LAER; RUYTER, 2010).…”
Section: Delimitação Do Tema E Definição Do Problemaunclassified